2011
DOI: 10.1021/jp110632g
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Based Surface-Hopping Dynamics Study on Ultrafast Internal Conversion in Cyclopropanone

Abstract: Cyclopropanone exhibits an intriguing phenomenon that the fluorescence from the S(1) state disappears below 365 nm. This is ascribed to the ultrafast S(1) → S(0) internal conversion process via conical intersection, which deprives opportunity of the fluorescence emission. In this work, we have used ab initio based surface hopping dynamics method to study vibrational-mode-dependent S(1) → S(0) internal conversion of cyclopropanone. A new conical intersection between the S(1) and S(0) states is determined by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 56 publications
3
40
0
Order By: Relevance
“…[9][10][11][12][13] Furthermore, ab initio NA-MD have been successfully applied to study ultrafast photoinduced electron transfer (ET) processes 14,15 in quantum dots, 16,17 and Auger phenomena including multiple exciton generation and recombination. 18 Among these methods, trajectory surface hopping algorithms have proven to be efficient techniques to describe the photochemistry of a variety of organic molecules such as benzene, 19 fulvene, azulene, 20 nucleobases, [21][22][23] poly(phenylene ethynylene) dendrimers, 74,75 formamide, 24 silaethylene, 25 ethylene, 26 azobenzene, 27,28 azomethane, 29 cyclopropanone, 30 and pyrrole 31,32 among others. Complexity a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] Furthermore, ab initio NA-MD have been successfully applied to study ultrafast photoinduced electron transfer (ET) processes 14,15 in quantum dots, 16,17 and Auger phenomena including multiple exciton generation and recombination. 18 Among these methods, trajectory surface hopping algorithms have proven to be efficient techniques to describe the photochemistry of a variety of organic molecules such as benzene, 19 fulvene, azulene, 20 nucleobases, [21][22][23] poly(phenylene ethynylene) dendrimers, 74,75 formamide, 24 silaethylene, 25 ethylene, 26 azobenzene, 27,28 azomethane, 29 cyclopropanone, 30 and pyrrole 31,32 among others. Complexity a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…After prolonged irradiation the bands from group C were clearly discernible, as shown in Figure 1(b). The photodissociation of cyclopropanone was studied experimentally [25] and theoretically [26][27][28]. Thomas and Rodriguez found that CH2=CH2 and CO were the only volatile products resulted upon excitation at a selected wavelength between 292 to 365 nm [25].…”
Section: Identification Of Additional Productsmentioning
confidence: 99%
“…and S0 states of cyclopropanone using the state-averaged CASSCF method; one leads to an α-bond fission and the other to two α-bond fissions [27,28]. phase, CH2COCH3 was detected [8].…”
Section: Identification Of Additional Productsmentioning
confidence: 99%
“…[1][2][3] It is attractive because it is easy to implement and offers an intuitive interpretation, and it has thus been adopted by many groups. [4][5][6][7][8][9][10][11][12][13][14][15][16] It has been applied to study many ultrafast photophysical and photochemical processes in the gas phase and the condensed phase. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Despite the growing popularity and success of the trajectory-based FSSH method, it remains approximate and has some well-known drawbacks.…”
Section: Introductionmentioning
confidence: 99%